Are there "women's crops"? A new tool for gender and agriculture. Issue 8 (16th November 2016) - Orr, Alastair; Homann Kee-Tui, Sabine; Tsusaka, Takujii; Msere, Harry; Dube, Thabani; Senda, Trinity
ABSTRACT: A "Gender Control Tool" was developed to measure women's control over decision-making for agricultural production, sales, and use of income. The tool was tested for groundnuts in Eastern Province, Zambia, where mechanisation has increased male participation in groundnut shelling, and for goats in Gwanda district, Zimbabwe, where the introduction of auctions has increased investment and sales. A mixed methods approach was used, that involved focus group discussions (FGDs) and a quantitative household survey. This article compares the results obtained from these two methods and discusses the strengths and weaknesses of the tool in understanding how commercialisation affects women's control.